Transtorno de déficit de atenção e hiperatividade e educação musical: três estudos no programa cordas da Amazônia - NOBRE, João Paulo dos Santos (Universidade Federal do Pará, 2012)
Attention Deficit Hyperactivity Disorder (ADHD) is a specific developmental disorder of high prevalence observed in children and adults, including impairments in behavior inhibition, sustained attention, resistance to distraction and regulating the activity level of individual facing some situations, being frequent the excessive motor behavior and inadequate. Due these characteristics, students with this disorder have accumulated impairments in several areas of life mainly in relation with the academic development. This has encouraged research as a way of developing behavioral technology to minimize the impact of this disorder in an individual’s life. Researchers in the field of music education have interested in this area objecting acknowledge in the way how music education can help students with ADHD to develop strategies to minimize the cost of learning for them. Thus, the purpose of this study was to investigate whether the music education can serve as an intervention tool to promote changes in the behavior repertoire of students with characteristics of risk to the disorder. The research was divided in three studies: screening prevalence of the disorder, analysis behavioral changes in students with characteristics of risk to ADHD and assessment of music learning. The results indicate that within of the sample studied (N=320), 52,18% presented score of compatible characteristics with the disorder. Regarding behavioral changes, we observed expansion of the repertoire of appropriate behaviors and reduction in the repertoire of inappropriate behaviors. When was established the assessment of learning music and comparison with a student with typical development, we observed that both students had a similar development.